Multiscale modeling of carbon nanotube epoxy composites. (23rd July 2015) - Alian, A.R.; Kundalwal, S.I.; Meguid, S.A.
Abstract: In this article, a multiscale modeling technique is developed to determine the effective elastic moduli of CNT-reinforced epoxy composites containing either well-dispersed or agglomerated carbon nanotubes (CNTs). Two aspects of the work are accordingly examined. In the first, molecular dynamics simulations are carried out to determine the atomic-level elastic properties of a representative volume element (RVE) comprised of either epoxy polymer or transversely isotropic CNT-epoxy composite. To study the effect of agglomeration of CNTs on the bulk elastic properties of the nanocomposite, CNT bundles of different sizes were considered. A constant-strain energy minimization method is used to determine the elastic coefficients of the RVEs. In the second, the Mori-Tanaka method is used to scale up the properties of the atomic structure to the microscale level, and the outcome is used to investigate the effect of orientations and agglomeration of CNTs on the bulk elastic properties of the nanocomposite. Our results reveal that as the number of CNTs in the bundle increases, the effective elastic properties of the nanocomposite decrease at the same CNT volume fraction. Graphical abstract: Highlights: Developed the novel multiscale model. MD simulations were used in conjunction with Mori-Tanaka model. Investigated the effect of orientations and agglomeration of CNTs. Current MD results are in good agreement with those of ABC results.